Effect of Recycled Aggregate Content on Water Permeability and Pore Structure of Pervious Concrete Pavement - Yin Cheng; Nan Shen; Hao Yu; Lu Feng; Tianjun Yang; Jun Shen (Advances in Materials Science and Engineering)
The shortage of natural aggregate (NA) and a large amount of construction waste generation bring opportunities for the application of recycled aggregate (RA). To investigate the mechanical properties and permeability of Recycled Aggregate Pervious Concrete (RAPC), this study tested the compressive strength, tensile strength, flexural strength, porosity, permeability coefficient, and water retention of RAPC with different RA contents (0, 25%, 50%, 75%, and 100%) and analyzed the changes of these parameters with RA content. Among them, two methods were used for the calculation of porosity. The results showed that the porosity, permeability, and water retention of RAPC increased with the increase in RA content, but the compressive strength, splitting tensile strength, flexural strength, and uniaxial tensile strength decreased. According to the demand of pavement engineering, RAPC should have good water permeability while meeting the strength requirements, so the optimal RA content is 50%.